Plato's Parmenides - Plato (University of California Press, 2003)
Of all Plato's dialogues, the 'Parmenides' is notoriously the most difficult to interpret. Scholars of all periods have disagreed about its aims and subject matter. This work presents a translation of the dialogue together with an introduction and commentary which provides an explanation of the 'Parmenides'.
Keywords: Socrates.; Parmenides.; Zeno, -- of Elea.; Plato. -- Parmenides.; Zeno, -- (of Elea.); Plato.; Parmenides; Socrates; Zeno, -- of Elea; Parmenides (Plato); Ontology -- Early works to 1800.; Reasoning -- Early works to 1800.; Dialectic -- Early works to 1800.; Ontologie -- Ouvrages avant 1800.; Dialectique -- Ouvrages avant 1800.; PHILOSOPHY -- History & Surveys -- Ancient & Classical.; Dialectic.; Ontology.; Reasoning.; Dialectic; Ontology; Reasoning; Humaniora -- Filosofi.; Early works